Recovery of the construction process for light housing roofsin awajún Condorcanqui comunities, Amazonas-Peru - Acuña Requejo, Marck Antony (2022)
Understanding the native reality and its identity is to revalue what is its own; For this reason, the objective of the investigation was the recovery of the construction process and the determination of the cost of covering the houses with the local palm trees Geonoma deversa "palmiche" and Phytelephas macrocarpa "yarina", existing in areas close to the town of Urakusa and Kayants. We proceeded to the identification, selection, cutting, folding, transfer and drying of the palm trees; Likewise, the leaves of the palm trees were placed or woven on the roof structure of a house previously built with joists and straps with the species Iriartea deltoidea, with 100% slope, using Paederia diffusa "liana" or "tamshi", achieving coverage aesthetic with yields of 11,76 m2/day and 26,64 m2/day for royal palm nuts and yarina respectively, with a cost per square meter of coverage of 24,46 soles with palm nuts and 8,73 soles with yarina.